THE ANALYSIS OF TEACHER’S TALK AND LEARNERS’ TALK IN CLASSROOM INTERACTION - Khatimah, Nur Husnil; Junaedi, Ahmad; Wahyuni, Wahyuni (elstic : english language linguistics culture, 2023)
This study aimed to analyze the type of teacher’s talk that occur in classroom interaction and the type of learners’ talk that occur in classroom interaction. The subjects for this research were students in the first-grade of SMPN 1 Majene. Researchers used the descriptive qualitative research as the research method. The research instruments were observation that was used in the classroom observation during the learning process. The results of this study were (1) The type of teacher’s talk that occurred the classroom interaction in the first-grade SMPN 1 MAJENE including two influences which are indirect influences including dealing with feelings, praising or encourage, joking, using ideas of students, repeating students’ verbatim, and asking questions; and direct influences including giving information, correction without rejection, giving direction, and criticizing students’ behavior; (2) The type of learners’ talk that occurred in the classroom interaction in the first-grade SMPN 1 MAJENE including response and silence or confusion.Keywords: Teacher’s talk, Learners’ talk, Classroom interaction